THE MEANING OF ORIGINALITY IN ARCHITECTURE AND HOW CAN IT BE MEASURED - Shareef, Vian Ahmed (Journal of process management and new technologies, 2018)
Abstract Meaning and different definitions for originality, meaning of originality in architecture, and the way of measuring it has been investigated in this research, which help researcher to compare between every two design product by using the applied criteria, in a straightforward method. Also, this research has determined the methods that architect can use to produce and increase the original idea in a research. Additionally, a number of samples have been taken as case studies to compare and evaluate originality in Architecture. Key words: Originality, originality in architecture, measuring originality in architecture, creativity, innovation